Robust design methodology for reliability : exploring the effects of variation and uncertainty - Bergman, Bo, 1943- (Chichester, U.K. : Wiley, 2009)
'The contributions of Exploring Unreliability and Its Countermeasures aim to address reliability problems in a constructive manner and offer a comprehensive design theory for reliability utilizing robust design methodology and six sigma frameworks. They advocate testing for robustness in the early stages of product design development, and consider varying uncertainties that are sometimes inherent in model assumptions for design solutions but which should not affect the system solution. Many companies today utilise design for Six Sigma (DfSS) for strategic improvement of the design process but often these initiatives do not explicitly describe the reliability perspective; this book explains how reliability design can relate to and work with DfSS and illustrates this with vivid illustrations from real - world problems. Advocates a new approach to reliability thinking that addresses the design process and proneness to failure in the design phase via sensitivity to variation management. Includes contributions from both academics and industry practitioners with a broad scope of expertise, including quality science, mathematical statistics and reliability engineering. Takes the innovative approach of promoting the study of variation and uncertainty as a basis for reliability work. Includes case studies and illustrative examples from real-world problems that translate the theory into practice'--Provided by publisher.
Includes bibliographical references and index
Keywords: Reliability (Engineering); Six Sigma (Quality control standard); Industrial design